Analysis of fungal bioaerosol contamination in residential area around a municipal landfill. - NEERAJ S. PATIL; UMESH B. KAKDE (International Journal of Pharma and Bio Sciences, 2017)
Landfill is an open space where municipal solid waste is disposed. Insanitary and poorly managed landfill sites can become potential threat for the people living around them. Such types of landfills provide organic matter for growth of microorganisms which leads to pollution of air with harmful gases as well as bioaerosols. Bioaerosols are fine biological particles suspended in air which contain fungal propagules, bacteria, actinomycetes etc. The present study deals with investigation of culturable aeromycoflora. The study was carried out in the year 2015-16 in the vicinity of Mulund landfill in Mumbai. The highest average concentration of fungal bioaerosol was registered in monsoon season which is 1081 cfu/m3 and the lowest average concentration recorded in winter season (346 cfu/m3). The Aspergillus species was the most abundant in the air. Other dominant species in the aeromycoflora were Penicillium, Alternaria, Cladosporium, Rhizopus, Mucor, Trichoderma etc. The concentration of bioaerosol is positively correlated with the Relative Humidity and Temperature.